2021
DOI: 10.1007/s12031-021-01801-1
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of AQP4/TRPV4 Channel Co-expression, Microvessel Density, and its Association with Peritumoral Brain Edema in Intracranial Meningiomas

Abstract: Apart from VEGF-A pathway activation, the existence of peritumoral edema (PTBE) in meningiomas has been correlated with the expression levels of water transporter aquaporin 4 (AQP4). A novel cooperation of AQP4 with the transient receptor potential isoform 4 (TRPV4), a polymodal swelling-sensitive cation channel, has been proposed for regulating cell volume in glial cells. We investigated AQP4/TRPV4 channel co-expression in meningiomas along with the neovascularization of tumors and associate with PTBE. Immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
(69 reference statements)
1
3
0
Order By: Relevance
“…This response of the AQP4 −/− /TRPV4 −/− mice to pMCAO indicates an interplay between these two channels, which was previously suggested in the experiments using cultured glia (Benfenati et al, 2011;Jo et al, 2015;Redmon et al, 2021) or in meningiomas (Faropoulos et al, 2021), where AQP4-mediated water fluxes promote the activation of TRPV4, whereas Ca 2+ entry through TRPV4 channels reciprocally modulates volume regulation, swelling, and Aqp4 gene expression (Jo et al, 2015). This interplay is especially prominent during the acute phase of ischemia, because after 7 days the damage detected in the AQP4 −/− /TRPV4 −/− mice was comparable to that observed in the Ctrl.…”
Section: The Deteriorating Effect Of Aqp4 or Trpv4 Deletion On The Si...supporting
confidence: 69%
See 1 more Smart Citation
“…This response of the AQP4 −/− /TRPV4 −/− mice to pMCAO indicates an interplay between these two channels, which was previously suggested in the experiments using cultured glia (Benfenati et al, 2011;Jo et al, 2015;Redmon et al, 2021) or in meningiomas (Faropoulos et al, 2021), where AQP4-mediated water fluxes promote the activation of TRPV4, whereas Ca 2+ entry through TRPV4 channels reciprocally modulates volume regulation, swelling, and Aqp4 gene expression (Jo et al, 2015). This interplay is especially prominent during the acute phase of ischemia, because after 7 days the damage detected in the AQP4 −/− /TRPV4 −/− mice was comparable to that observed in the Ctrl.…”
Section: The Deteriorating Effect Of Aqp4 or Trpv4 Deletion On The Si...supporting
confidence: 69%
“…The activation of TRPV4 channels increases intracellular Ca 2+ concentration, which triggers RVD and leads to water efflux via the AQP4 channels and, therefore, strongly affects the cellular response to the development of cytotoxic brain edema (Benfenati et al, 2011;Jo et al, 2015). In addition, recent study showed correlation between the increased expression of AQP4/TRPV4 complex and larger peri-tumor edema in patients (Faropoulos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Piezo1 have been suggested as potential prognostic biomarkers for the early diagnosis of glioma, 140 , 141 given the level of Piezo1 is positively correlated with the severity of edema and the degree of compression forces. 142 , 143 , 144 …”
Section: The Mscs Respond To Forces From Place‐occupying Damagementioning
confidence: 99%
“…TRPV4 has, in addition, been implicated in pulmonary edema formation, partly via the observed down regulation of the co-localized AQP5 in the pulmonary epithelium obtained from TRPV4 - / - mice ( 27 ). Tissue obtained from meningioma patients demonstrated AQP4/TRPV4 co-expression in both edematous and non-edematous meningiomas, although in the surrounding peri-meningioma tissue, only AQP4 was upregulated ( 28 ). TRPV4 thus appears to be involved in physiological and pathophysiological processes involving fluid dynamics, in addition to its roles in skeletal dysplasias [for review of TRPV4 in pathology, see ( 29 )].…”
Section: Cellular Detection Of Volume Changesmentioning
confidence: 99%